2017
DOI: 10.2147/ijn.s142122
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of human arthritis synovial fibroblasts inflammation using dexamethasone-carbon nanotubes via increasing caveolin-dependent endocytosis and recovering mitochondrial membrane potential

Abstract: Dexamethasone (DEX), a non-particulate glucocorticoid (GC) to inhibit anti-inflammatory response, has been widely used for the treatment of various diseases such as arthritis, cancer, asthma, chronic obstructive pulmonary disease, cerebral edema, and multiple sclerosis. However, prolonged and/or high-dose GC therapy can cause various serious adverse effects (adrenal insufficiency, hyperglycemia, Cushing’s syndrome, osteoporosis, Charcot arthropathy, etc). In this study, developed DEX-carbon nanotube (CNT) conj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Moreover, we studied the mechanism underlying the cellular endocytosis of CNPs in kidney cells. In consistent with previously reported PEGylated nanoparticles 42 , the cellular uptake of CNPs is reduced in the presence of MβCD, chlorpromazine, and amiloride, respectively, indicating that CNPs can be internalized into HK-2 cells via multiple pathways, among which the caveolin-mediated endocytosis plays a major role in the cellular uptake of CNPs 42 (Supplementary Fig. 18 ).…”
Section: Resultssupporting
confidence: 90%
“…Moreover, we studied the mechanism underlying the cellular endocytosis of CNPs in kidney cells. In consistent with previously reported PEGylated nanoparticles 42 , the cellular uptake of CNPs is reduced in the presence of MβCD, chlorpromazine, and amiloride, respectively, indicating that CNPs can be internalized into HK-2 cells via multiple pathways, among which the caveolin-mediated endocytosis plays a major role in the cellular uptake of CNPs 42 (Supplementary Fig. 18 ).…”
Section: Resultssupporting
confidence: 90%
“…A membrane-permeant dye JC-1 is widely used in apoptosis studies to monitor the status of mitochondria where JC-1 accumulates in a potential-dependent manner as indicated by a fluorescence emission shift from green (~ 529 nm) to red (~ 590 nm). Accordingly, mitochondrial polarization (healthy state) or depolarization (damaged state) can be revealed by an increase or decrease, respectively, in the red/green fluorescence intensity ratio (Lee et al 2017 ). Confocal microscopy images showed that in control cells, mitochondria exhibited strong red JC-1 fluorescence indicative of Δ ψm polarization, which was reduced in PM 2.5 -treated cells where green fluorescence indicative of Δ ψm depolarization was increased; however, the effect was suppressed by NAC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nanomaterials designed for delivery to the synovium have been engineered in sizes ranging from 5nm to 300nm and with a range of materials including synthetic polymers [132,133], polysaccharides [134][135][136][137], carbon-nanotubes [138], micelles [139], liposomes [140], and lipids [141]. When targeting synoviocyte-acting drugs to the synovium, both the size and composition of nanomaterials are critical factors to control the degree of tissue penetration and transport between the synovium and the synovial fluid.…”
Section: Passive Targeting To the Synoviummentioning
confidence: 99%